Child functioning in inclusive preschools: Associations between self-regulation, engagement, prosociality, and hyperactivity - Coelho, Vera (2023)
This longitudinal study examined three groups of children with different levels of developmental functioning who were attending the same inclusive preschool classrooms. It investigated whether gains in self-regulation varied according to developmental functioning and whether the longitudinal associations between selfregulation and later engagement, prosociality, and hyperactivity differed between children with low, medium, and high levels of functioning. Participants comprised 247 preschoolers. Fifty-four were low functioning, 78 were low-medium functioning, and 115 were medium-high functioning. All groups improved their self-regulation over time, though initial levels and growth patterns were different. Children with low-medium functioning showed more accelerated gains than the other groups. Gains in self-regulation were associated with lower hyperactivity and higher engagement in all groups by the end of preschool. Developmental functioning was related to later prosociality and engagement. The results revealed potential differentiated trajectories for children within the same classrooms, highlighting the interdependence of developmental functioning and self-regulation.